Pengaruh Efisiensi Operasional dan Kualitas Layanan terhadap Kepuasan Nasabah pada Office Chanelling Syariah Bank Sumsel Babel Capem Bayung Lencir - Merly Suzana; Patriana Patriana; Chinta Yurike Utomo; Rendra Novia Deska; Novi Mubyarto; Titin Agustin Nengsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of operational efficiency and service quality on customer satisfaction in the Sharia Office Channeling service at Bank Sumsel Babel. Customer satisfaction is one of the key indicators used to evaluate the success of banking services, particularly in Sharia Office Channeling services, which play an important role in expanding public access to Islamic banking services. Therefore, operational efficiency and service quality are essential factors that need to be considered in order to enhance customer satisfaction. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 108 customers as research respondents. The data were analyzed using validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results showed that all research instruments were valid and reliable, with a Cronbach’s Alpha value of 0.980. The regression equation obtained was Y = 0.382 + 0.806X₁ + 0.125X₂. The partial test results indicated that operational efficiency had a positive and significant effect on customer satisfaction with a significance value of 0.000 (< 0.05), while service quality did not have a significant partial effect on customer satisfaction with a significance value of 0.314 (> 0.05). However, simultaneously, operational efficiency and service quality had a significant effect on customer satisfaction with a significance value of 0.000 (< 0.05). The coefficient of determination (R²) was 0.777, indicating that 77.7% of the variation in customer satisfaction could be explained by operational efficiency and service quality, while the remaining 22.3% was influenced by other factors outside the research model. The findings indicate that operational efficiency is the most dominant factor in improving customer satisfaction, particularly through the speed, accuracy, and smoothness of service processes. Therefore, improving operational efficiency should be a primary priority in efforts to enhance customer satisfaction in the Sharia Office Channeling service at Bank Sumsel Babel Bayung Lencir Sub-Branch Office